Assessing cognitive toxicity in early phase trials ‐ What are we missing?. Issue 3 (29th October 2021) - Stapleton, Sarah E.; Darlington, Anne‐Sophie; Minchom, Anna; Pal, Abhijit; Raynaud, Florence; Wiseman, Theresa
Abstract: Objectives: Novel therapies, such as, small protein molecule inhibitors and immunotherapies are first tested clinically in Phase I trials. Moving on to later phase trials and ultimately standard practice. A key aim of these early clinical trials is to define a toxicity profile; however, the emphasis is often on safety. The concern is cognitive toxicity is poorly studied in this context and may be under‐reported. The aim of this review is to map evidence of cognitive assessment, toxicity, and confounding factors within reports from Phase I trials and consider putative mechanisms of impairment aligned with mechanisms of novel therapies. Methods: A scoping review methodology was applied to the search of databases, including Embase, MEDLINE, Clinicaltrials.gov . A [keyword search was conducted, results screened for duplication then inclusion/exclusion criteria applied. Articles were further screened for relevance; data organised into categories and charted in a tabular format]. Evidence was collated and summarised into a narrative synthesis. Results: Despite the availability of robust ways to assess cognitive function, these are not routinely included in the conduct of early clinical trials. Reports of cognitive toxicity in early Phase I trials are limited and available evidence on this shows that a proportion of patients experience impaired cognitive function over the course of participating in a Phase I trial. Links are identified between the targeted action of some novel therapies and putative mechanisms of cognitive impairment. Conclusion: The review provides rationale for research investigating cognitive function in this context. A study exploring the cognitive function of patients on Phase I trials and the feasibility of formally assessing this within early clinical trials is currently underway at the Royal Marsden.